Deus e o diabo na terra do sol: crise, conservadorismo e necessidade do mal no Brasil contemporâneo - Frederico Rodrigues Bonifacio (2018)
In this study we strive for understand the fundamentals of the ongoing crisis in Brazil, as well as disentangle which makes possible the wide advancement of right and conservatism in the country in recent years (2013-2017). The universality of a whole fragmented, reified, as the imperatives of certain sociability for the equivalent fetish provides the backdrop, the ground on which the peculiarities of the Brazilian context is based. So we set out the general terms of this universal: awareness allocated under the subject form and its inherent contradictions, the determinations of the modern real abstraction that give reality a metaphysical aspect directly lived, totalitarianism of democracy under the state form and its real impossibilities and as the limits presented by the form of value as its unlimited that requires enhancement to thus achieve their particular terms. Namely, the development of the authoritarian personality in the Brazilian context, the need for personification of evil in the Party's figure of Workers and their participants, the weakness of Brazilian democracy and its regression to forms of institutionalized totalitarianism and the materiality of the economic crisis expressed in a state exception that makes the rule itself in the production of space and life as a whole.